Plan de negocios para la creación de un plantel avícola comunitario y comercialización en la provincia de Cotopaxi, cantón Latacunga, parroquia Mulaló - Moreno Castro, Jenny Patricia (2016)
This work was developed with the aim of creating a Community poultry flock in the province of Cotopaxi, Latacunga Canton, Parish Mulaló to meet the unmet demand for the product. For research methodology direct research inductive and analytical method we were used , by using tools for gathering information as the survey that was applied to the population of Mulaló , giving as main result the acceptance of the product the area and obtaining a significant unmet demand to launch our product to market. For the creation of the poultry flock we perform a technical and financial study to determine the location of the business, installed capacity, and financial feasibility indicators that lead us to determine business success….